Pollen metabarcoding reveals the floral resources and niche overlap of honeybees in forest areas. Issue 12 (30th November 2022) - Do, Yuno; Park, Woong‐Bae; Park, Jun‐Kyu; Kim, Chang‐Jun; Kim, Il‐Kwon; Choi, Moon Bo
Abstract: We investigated the floral resources of the honeybee ( Apis mellifera ) by pollen DNA metabarcoding as the first step in honeybee conservation. We attempted to identify as many floral resources and as wide resource availability as possible in areas and compared the richness of floral resources between forests and national parks. We found that both forest and national parks can sufficiently support honeybee floral resources; however, national parks were more stable habitats with more complex vegetation structure than those of forests. Also, honeybee's preferences for floral resources were determined using niche breadth, niche overlap, and network analysis among the floral resources in forest areas. Quercus and Actinidia were the most frequently detected taxa of pollen resources in both forests and national parks by pollen metabarcoding. Even though we anticipated that more various pollen resource taxa would be found in national parks than forests, no differences in the number pollen resource taxa were detected between them. According to the niche overlap analysis result, the honeybee preferred the pollen resources in both forests and national parks, and the co‐occurrence pattern analysis of pollen resource taxa in both forests and national parks showed a simple network. Altogether, our findings suggested that DNA metabarcoding of pollen collected by the honeybee can provide useful information on the flowering plants in a given area. As the use of floral pollen resources varies spatially and temporally, periodic monitoring of pollen resources can identify which pollen is required to maintain the health of honeybee colonies.